2008
DOI: 10.1161/circulationaha.107.757617
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myoblasts Preserve Remote Matrix Architecture and Global Function When Implanted Early or Late After Coronary Ligation Into Infarcted or Remote Myocardium

Abstract: Background-The inability of skeletal myoblasts to transdifferentiate into cardiomyocytes suggests that their beneficial effects on cardiac function after a myocardial infarction are mediated by paracrine effects. We evaluated the roles of these factors in the preservation of matrix architecture (in the infarct and remote regions) by varying the timing (postmyocardial infarction) and delivery site of the implanted cells. Methods and Results-Skeletal myoblasts (5ϫ10 6 ) or control media were injected into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Further, injection of mesenchymal stem cells has been shown to improve cardiac function in rats by preserving remote matrix architecture and preventing ventricular dilation [20]. These two-photon results support the hypothesis that both limitation of collagen accumulation in the scar and prevention of necrosis of myocytes in the infarct region may be potential mechanisms of functional improvement by stem-cell regeneration.…”
Section: Injury and Regeneration Mechanismssupporting
confidence: 62%
“…Further, injection of mesenchymal stem cells has been shown to improve cardiac function in rats by preserving remote matrix architecture and preventing ventricular dilation [20]. These two-photon results support the hypothesis that both limitation of collagen accumulation in the scar and prevention of necrosis of myocytes in the infarct region may be potential mechanisms of functional improvement by stem-cell regeneration.…”
Section: Injury and Regeneration Mechanismssupporting
confidence: 62%
“…Thus, Li et al [37] investigated the outcome of fetal CM injected in a rat model of cryoinjury, showing that no transplanted cells were found 8 weeks after when immediately transplanted after injury, whereas CM injected 2 or 4 weeks later, when inflammation had disappeared, formed new tissue and positively affected cardiac function. Conversely, the group of Dr. Li found that injection of SkMyo, either in the infarcted or non-infarcted area of rats subjected to MI, induced a significant effect on cardiac contraction indistinctly of the time of injection (5 or 30 days post-MI) [16]. This group also found that the benefit was related to a greater prevention of ventricular dilatation and preservation of ECM architecture through influence in the MMP/TIMP system.…”
Section: Some Aspects Of Stem Cell Transplant To Considermentioning
confidence: 98%
“…In spite of their lack of differentiation capacity [31] and their arrhythmyogenic potential [46], myoblast are able to act in a paracrine manner, secreting molecules capable of increasing the vascularization of the site as well as reorganizing the ECM [63]. In a rat model of chronic MI, Bonaros et al [7] showed that skeletal myoblasts (SkMyo) transplantation significantly affected ventricular function 1 month after injection which was later confirmed by Farahmand et al [16] who also found that the benefit was independent of the site of injection (into the infarction or in the remote zone). Moreover, Fukushima et al [20] reported that SkMyo transplantation either through the coronary veins or intramyocardially was beneficial for cardiac function and that this benefit was long-lasting (up to 3 months).…”
Section: Skeletal Muscle-derived Cellsmentioning
confidence: 99%
“…After a period of 30 days, the animals were anesthetized and ventilated, as previously described, for echocardiographic examination, as described by Farahmand et al [18]. After tricotomy of the anterior thoracic region, the animals were placed in dorsal decubitus in a heated surgical bed for the appropriate positioning of the transducer in the left hemithorax of the animal.…”
Section: Echocardiographic Examinationmentioning
confidence: 99%